Superior performance of N-doped carbon Nanoonions/Nafion based microfluidic electrochemical Cd2+ sensor when compared to Screen-Printed Carbon-Based electrode devices - Ghanbari, Mohammad Hossein; Norouzi, Zahra; Biesalski, Markus; Etzold, Bastian (Microchemical Journal, 2024)
The sensing of cadmium is important due to its highly toxic effects on various organs of humans and animals. Commonly employed are screen-printed carbon-based electrodes (SPCE) as suitable low-cost sensing platform. Microfluidic electrochemical sensor (μCS) can also be portable, highly sensitive, and low-cost but are up to now only seldom studied and applied. Here we demonstrate the superior performance of μCS over SPCE arrangements for sensing ultra-trace of Cd2+. Additionally, N-doped carbon nanoonions (N-CNOs) are introduced as sustainable non-metallic modifier and employed for both sensing arrangements. The study depicted that employing the modifier the electrochemically active surface area and the electron transfer rate in both arrangements is improved together with improve sensitivity. Both arrangements were compared using cyclic voltammetry and electrochemical impedance spectroscopy in [Fe(CN)6]3−/4−, and also square-wave anodic stripping voltammetry (SWASV) for Cd2+ sensing. The µCS arrangement clearly outperforms the SPCE arrangement in signal strength. For the final device (μCS modified with N-CNOs) a linear concentration range from 1.0 to 100 μg L−1 was achieved. The limit of detection and sensitivity resulted to 0.25 μg L−1 and 1.02 μA µg−1 L cm−2, respectively. Besides this excellent sensitivity combines with high stability, which was tested for 8 repetitive measurements with a single device resulting in high reproducibility. Additionally, this procedure was favorably employed for measurements of Cd2+ in different real samples, which demonstrated the excellent applicability of the device for the adsorption and detection of heavy metal ions.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Cadmium; Microfluidic electrochemical sensor; N-doped carbon nanoonions; Screen-printed carbon-based electrode